2009
DOI: 10.1038/nature08689
|View full text |Cite
|
Sign up to set email alerts
|

Large, rare chromosomal deletions associated with severe early-onset obesity

Abstract: Obesity is a highly heritable and genetically heterogeneous disorder1. Here we investigated the contribution of copy number variation to obesity in 300 Caucasian patients with severe early-onset obesity, 143 of whom also had developmental delay. Large (>500 kilobases), rare (<1%) deletions were significantly enriched in patients compared to 7,366 controls (P < 0.001). We identified several rare copy number variants that were recurrent in patients but absent or at much lower prevalence in controls. We identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
434
3
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(463 citation statements)
references
References 25 publications
18
434
3
8
Order By: Relevance
“…2,4,6,7,9,15,17 As shown by 4C-seq, FISH, and Hi-C, the two 16p11.2 CNV-prone regions are reciprocally engaged in evolutionary-conserved complex chromatin looping, as well as coordinated expression of encompassed genes. 17,45 Here we assessed whether these findings were paralleled by genetic interactions between the 28 and 9 single-copy genes within the 16p11.2 600 kb BP4-BP5 and 220 kb BP2-BP3 intervals, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,6,7,9,15,17 As shown by 4C-seq, FISH, and Hi-C, the two 16p11.2 CNV-prone regions are reciprocally engaged in evolutionary-conserved complex chromatin looping, as well as coordinated expression of encompassed genes. 17,45 Here we assessed whether these findings were paralleled by genetic interactions between the 28 and 9 single-copy genes within the 16p11.2 600 kb BP4-BP5 and 220 kb BP2-BP3 intervals, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] The deletion of the distal 16p11.2 220 kb BP2-BP3 locus (MIM: 613444) is likewise enriched in individuals with early-onset obesity and is also associated with developmental delay, intellectual disability, autism spectrum disorders (ASD), and schizophrenia. 3,[13][14][15][16] Moreover, the BP2-BP3 deletion and reciprocal duplication have mirror effects on BMI and HC, whereas the duplication of this interval, like the deletion, is associated with ASD. 17 Thus, genomic rearrangements at both the 16p11.2 600 kb BP4-BP5 and the 220 kb BP2-BP3, two loci 650 kb apart, present similar clinical patterns: large effect sizes on BMI and HC, as well as association with ASD and other neuropsychiatric traits.…”
Section: Introductionmentioning
confidence: 99%
“…The region in question has PPYR1 gene, regulating energy balance. 57,58 Amylase gene CNVs is found not only contributing to the disease in general but also is found to be involved with diet, such as salivary amylase gene (AMY1 gene), which is associated with the starchy food consumption in a population. It has been reported that higher copy number of AMY1 gene is correlated positively with salivary amylase protein levels and a population with high-starch food consumption has higher copy number of AMY1 gene and improves the digestion of starchy foods and may reduce the burden of intestinal diseases.…”
Section: Cnv and Susceptibility To Other Common Disorders Hiv/aids Sumentioning
confidence: 99%
“…[19][20][21] Similarly, the importance of rare variants in complex diseases is also being recognized. 56,90,115,116 This implies that future disease association studies need to interrogate non-SNP and rare genetic variations as well, and for this to be feasible, a detailed catalog of human genetic variations is a prerequisite. Common SNPs are well documented in the dbSNP, but rarer SNPs (or lower frequency SNPs) are still under-represented in the database and the information of indels and structural variations is far from complete.…”
Section: Copy Neutral Variations-inversions and Translocationsmentioning
confidence: 99%